Penggunaan Teknik Evaluasi Non Tes Pada Pembelajaran IPS Kelas VI di SD Negeri 1 Pengkelak Mas - Hapiz, Abd (FAKULTAS TARBIYAH, 2020)
This study aims to determine the implementation of non-test evaluation in social studies learning at SD Negeri 1 Pengkelak Mas The method used is a qualitative method (qualitative description) with the aim of describing, analyzing phenomena, events, and social studies learning evaluation activities carried out by teachers to grade 6 students SD Negeri 1 Pengkelak Mas Data collection techniques used were observation, interviews with teachers, interviews with school principals, documentation, field notes, and triangulation. Triangulation is a technique of collecting data by combining several existing data combining techniques and data sources. The results showed that in general, the quality of social studies learning at SD Negeri 1 Pengkelak Mas had a good process. Likewise, the learning output has also obtained good results. However, in the implementation of social studies learning there are also things that need to be addressed in order to improve the learning program